The wild indoors: Room-spaces of scientific inquiry - Lezaun, J; Kelly, A (American Anthropological Association, 2017)
This paper examines three locations where entomologists engage in the experimental observation of mosquitoes: the insectary, the semi-field station, and the outdoors. We approach each of these settings as creating a distinct mode of interiority, a particular room-space. This concept resets the investigative encounter in terms of an aesthetic of attention, and offers a counterpoint to the ideals of ‘control’ and ‘containment’ that dominate biosecurity understandings of infectious disease research. An ethnographic foray into the compositional logics of entomological experiments serves to illuminate the dialectics of caring and killing that characterize scientific inquiry into animals that pose a public health risk.